Outcomes of Financial Dashboard Development, Warinchamrab District, Ubonratchathani Province - มณี, สถาพร; ตางาม , ลำใย; บุญมา, ทวีภรณ์; พลอำนวย , ณภัค; สิมานุรักษ์ , ฐินันท์พัทธ์ (Journal of Health Science of Thailand, 2025)
Hospital financial management requires accurate, complete, and timely information to be used for planning, controlling, and evaluating financial performance. This study aimed to investigate the outcomes of developing a financial reporting information system for administrators and practitioners in hospital. This action research conducted at Warinchamrab Hospital, Ubon Ratchathani Province between October 2022 and September 2023, used a design thinking approach with five steps: (1) empathize; (2) defined; (3) ideate; (4) prototype; and (5) test. The financial reporting information system has 9 sub- components: financial status, financial plan, revenue, performance, cost and expenses, total performance score, efficiency, investment, and human resource development budget control. The results indicated that the development of the financial dashboard led to cost reduction, decreased steps and working time, provided online access to data, was customizable to meet user requirement, enhanced security, and supported teamwork. The system performance testing results showed that user feedback from 45 participants, most were female (82.2%), 46.7% in the 31-40 age range, 62.2% being front-line staff, and 68.9% having more than 10 years of experience. The overall score was found to be 82.2%, with ease of use, responsiveness to user needs, efficiency, and safety being 83.3, 83.3, 81.7, and 79.4%, respectively. In terms of usefulness, all participants agreed that the system was beneficial for providing financial information, quality improvement, and data for research. In conclusion, the development of the hospital financial reporting information system for Warinchamrab Hospital improved the efficiency and effectiveness of hospital operations, which led to cost reduction, decreased steps and working time, and enabled transparent online access to financial status for users with overall user feedback indicated high satisfaction.